Creating Assets as a Part of Tertiary Education of Technical Domains - Brožek, Josef; Kopecký, Zbyněk; Hamerník, Dan (IEEE (Institute of Electrical and Electronics Engineers), 2016)
Game engines are becoming the forefront interest of modern-game developers. Budget savings caused by simplification of work with 3D graphics, physics, and event oriented scripting are benefits that may provide game studios with a competitive advantage. Because university education should reflect technological advances in the IT field, a concept was created on how to include Asset creation into the curriculum of tertiary education. The introductory part of the article is dedicated to Assets; it sums their principle, base benefits and practical use. The article focuses on the specifics of implementation of Asset-based education into the education process of key subjects, and monitors the results of these changes.
Tvorba assetů jako část technického vysokoškolského vzdělávání
Keywords: Creating; Assets; Part; Tertiary; Education; Technical; Domains